Group 2 innate lymphoid cells drive inhibitory synapse formation with lasting effects on learning and memory - Johannes Steffen; Divija Deshpande; Henning Peter Düsedau; Janna Schmitz; Caio Andreeta Figueiredo; Laura Velleman; Claudia Pitzer; Christoph S.N. Klose; Ildiko R. Dunay (Journal of Neuroinflammation)
Abstract The immune system provides multiple layers of protection that extend beyond conventional pathogen defense, including context-dependent modulation of behavior. However, the mechanisms driving these immune-mediated behavioral modifications remain incompletely understood. Here, we demonstrate that group 2 innate lymphoid cells (ILC2s) shape hippocampal synaptic development during early postnatal stages, with lasting effects on adult behavior, learning, and memory. Using flow synaptometry, we identified a selective reduction in hippocampal VGAT+ GABAergic/glycinergic inhibitory synapse frequency at postnatal day 15 in ILC2-deficient mice, while the proportions of inhibitory GABAergic (NL2+) or excitatory glutamatergic (GluR1+) synapses remained unaltered. These synaptic changes occurred without detectable phenotypical changes in cortical and hippocampal microglia. In adulthood, ILC2-deficient mice displayed significant impairments in hippocampus-dependent tasks, such as active place avoidance and operant conditioning, reflecting deficits in learning and memory. Our findings reveal a critical role for ILC2s in the formation of inhibitory synapses in the hippocampus, highlighting the impact of immune signaling on neuronal network maturation during a crucial period of brain development. This early immune-mediated modulation may have lasting effects on neuronal circuitry and cognitive functions that persist into adulthood, emphasizing the long-term implications of neuro-immune interactions for normal cognitive development and function.